Compliance with Global Best Practices by Garment Producers in Ghana - Stella Daah Siaw; Ebenezer Kofi Howard; Ninette Afi Appiah; Cynthia Akua Chichi; Benjamin Kwablah Asinyo (Fashion and Textiles Review)
Purpose: This study investigates the level of compliance with global best practices among garment producers in Ghana, with a specific focus on sourcing compliance, production compliance, and distribution compliance. It covers aspects such as labour ethics, environmental stewardship, product quality, and adherence to international trade standards.